Assessment of Functional Capacity of Immune System in Patients with Multiple Sclerosis using QuantiFERON Monitor. (7th April 2023) - Pavelek, Zbysek; Soucek, Ondrej; Krejsek, Jan; Sejkorova, Ilona; Vysata, Oldrich; Klimová, Blanka; Angelucci, Francesco; Stourac, Pavel; Valis, Martin; Peterka, Marek; Sobisek, Lukáš; Novotny, Michal
Abstract : Background . The QuantiFERON®-Monitor (QFM) is an assay that measures interferon- γ production and was developed to provide an objective marker of complex immune response. In this study, we evaluated the use of the QFM test in patients with two forms of multiple sclerosis (MS), relapsing–remitting form treated with fingolimod (fMS) and secondarily progressive form not treated pharmacologically (pMS), and in healthy controls (HC). We hypothesized that IFN- γ levels would be lower in those subjects who are relatively more immunosuppressed and higher in those with normal or activated immune function. Methods . This single-center observational study was conducted from November 2020 to October 2021 and compared results in three groups of patients: 86 healthy controls, 96 patients with pMS, and 78 fMS. Combination of lyophilized stimulants was added to 1 ml heparinized whole blood within 8 hr of collection. Plasmatic IFN- γ was measured using the ELISA kit for the QFM and data were obtained in IU/ml. Results . The results showed that controls had nearly 2-fold higher levels of IFN- γ (QFM score) in median (q25, q75) 228.00 (112.20, 358.67) than the MS patient groups: pMS 144.80 (31.23, 302.00); fMS 130.50 (39.95, 217.07) which is statistically significant difference P -value: HC vs. pMS = 0.0071; HC vs. fMS = 0.0468. This result was also confirmed by a validation analysis to exclude impact of variable factors, such as disease duration and Expanded Disability Status Scale scores. Conclusions . Results showed that controls had higher levels of IFN- γ production than the MS patient groups and suggest that MS patients included in this study have a lower ability of immune system activation than HC. Results confirm that fingolimod is able to suppress production of IFN- γ . The fact that the QFM score of MS patients is significantly lower than that of HC may indicate a dysfunctional state of the immune system in baseline conditions.